PERSONALITY TRAITS AND READING STRATEGY USE IN EFL LEARNING - Agus Budiarte; I Wayan Putra Adi Subawa; Ida Bagus Gde Phalaguna (IKIP SARASWATI TABANAN, 2026)
This study investigated the relationship between personality traits and reading strategy use among early-stage EFL learners. Employing a quantitative correlational design, the study involved 21 second-semester English education students. Data were collected using the Big Five Inventory (BFI) and the Survey of Reading Strategies (SORS), and analyzed using Pearson Product–Moment correlation. The findings revealed that personality traits influence reading strategy use selectively. Among the five traits, Agreeableness emerged as the most consistent and significant predictor across global, problem-solving, and support strategies. In contrast, Conscientiousness and Neuroticism were significantly associated only with problem-solving strategies, indicating the role of both cognitive control and emotional factors in handling reading difficulties. Extraversion and Openness did not show significant relationships with any strategy type. These results suggest that social and interpersonal characteristics play a more prominent role than other personality dimensions in shaping strategic reading behavior. The study highlights the importance of considering individual differences in reading instruction and recommends integrating strategy-based and learner-centered approaches in EFL classrooms. Future research is encouraged to involve larger samples and explore additional variables to gain deeper insights into the relationship between personality and language learning strategies